Pengimplementasian Pembelajaran Jarak Jauh melalui Modul E-Learning Berbasis Layanan Cloud - Chris Pontonio; Calvin Calvin; Rio Fernando; Vincent NG (Journal of Information System and Technology (JOINT), 2022)
Cloud computing is starting to be heard a lot and is growing rapidly which provides convenience and comfort. Cloud computing has a significant impact in the Education and learning environment, enabling users to perform tasks more effectively and affordably by leveraging cloud-based applications available by cloud service providers. The role of technological developments in the world of education is growing very rapidly, especially in the use of e-learning. e-learning facilitates the teaching and learning process in digital form which is carried out using electronic media. Keywords : E-learning, Cloud Computing, Electronic Media